A wearable visible and infrared dual-band stealth material and preparation method thereof

By depositing gold particles on the double-pass porous material substrate to form a gold film and gold column structure, and combining a high-temperature resistant metal oxide protective layer, it is solved in the prior art that it is difficult to design a material problem that is both visible and infrared dual-band stealth, high temperature resistance, light weight and wearable, and achieves efficient stealth effect and good material performance.

CN116005116BActive Publication Date: 2025-03-04NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211742559.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-31
Publication Date
2025-03-04
Estimated Expiration
2042-12-31

AI Technical Summary

Technical Problem

It is difficult to design a material that has both visible and infrared dual-band stealth, high temperature resistance, light weight, wearable, and simple process.

Method used

Using a dual-pass porous material as the substrate, gold particles are deposited through electron beam evaporation to form a gold film and gold column structure, and combining a high-temperature resistant metal oxide protective layer to prepare an ultra-thin visible and infrared dual-band stealth material.

Benefits of technology

It achieves high absorption rate (91.2%) in the visible light band and low emissivity (3.5%) in the infrared band, and is ultra-thin, lightweight, good dependence and breathability, suitable for high temperature conditions and wearable applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116005116B_ABST
    Figure CN116005116B_ABST
Patent Text Reader

Abstract

The present invention relates to a wearable visible and infrared dual-band stealth material and a preparation method thereof, which specifically comprises the following steps: using a double-pass porous material as a substrate, evaporating gold particles on the substrate material by electron beam evaporation to form a composite device of the substrate material and gold; placing the formed composite device in a reaction liquid to react, dissolving the substrate material in the reaction liquid, leaving a gold structure; depositing a high-temperature resistant metal oxide on one side where a gold column is set, and the deposition thickness is nanometer-scale. The obtained stealth material has dual stealth characteristics of visible and infrared through the localized plasmon effect between the gold particles, and at the same time, because of its large number of pores, it provides comfortable wearing characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a stealth material, in particular to a wearable visible and infrared dual-band stealth material. Background Art

[0002] Achieving visible and infrared compatible stealth is crucial in the field of national defense. For visible stealth, achieving stealth in a dark environment is an important application scenario, which requires the material to have a high absorption rate in the visible light band (0.38-0.78μm). For infrared stealth, the fundamental thing is to reduce the radiation power of the high-temperature target object and make it as close as possible to the radiation power of the surrounding low-temperature environment, so as to achieve the effect of camouflaging the high-temperature object into the surrounding environment in the infrared detector, reducing the probability of being detected.

[0003] According to the Stefan Boltzmann equation (P = εδT 4 ) It can be seen that the radiation power of an object is proportional to the emissivity of the object and the fourth power of the temperature. Therefore, the existing technology usually starts from two angles to effectively reduce the radiation power of the material. One is to reduce the surface temperature of the material. This method usually places a material with low thermal conductivity, such as SiO, on the surface of the high-temperature object. 2 Gel, or phase change material GST, VO 2 The disadvantage is that in order to effectively reduce the surface temperature of the material, especially when the temperature is very high, the low thermal conductivity or phase change material required is thick and heavy, which limits its practical application. Another method is to reduce the emissivity of the material surface, which is currently the most important and effective way to reduce the radiation power of the material. Common low emissivity materials include metals such as gold, silver, aluminum and stainless steel.

[0004] However, when considering the realization of visible and infrared compatible stealth in a dark environment, it can be found that common materials in nature are difficult to meet this demand. For example, carbon materials are optically black and have a high absorption rate in the visible band, but their high emissivity in the infrared band limits their application. Similarly, for ordinary bulk metal materials, although they have extremely low emissivity in the infrared, they are usually visible as gold, silver, etc., with obvious metallic luster, which does not meet the requirements of dual-band compatible stealth. Therefore, the existing technology usually requires artificial fine design of some structures and materials, such as metamaterials, multilayer films, etc. However, metamaterials often involve some nano-sized, finely arranged structures, which correspond to the requirements of micro-nano processing technology, such as photolithography, etc., which are expensive and difficult to mass produce, and the fine structure is usually a metal material, which undergoes melting structure destruction at high temperature, thereby failing. At the same time, the design of multilayer films usually requires fine film thickness control, the process is relatively complex, the overall material is relatively thick, up to tens of microns, and is not suitable for high temperature conditions. In addition, metamaterials and multilayer films are usually dense and non-porous structures, without air permeability, and do not have wearable properties.

[0005] Therefore, it is urgent to design a dual-band compatible stealth material with excellent performance, simple process, high temperature resistance, light weight, and wearable potential. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-thin visible and infrared dual-band stealth material suitable for high temperature conditions with adherence and wearable potential. In view of the above purpose, the stealth material of the present invention and the preparation method of the material are provided. The obtained stealth material has dual stealth properties of visible and infrared through the localized plasmon effect between gold particles. At the same time, due to its many pores, it provides comfortable wearing characteristics.

[0007] The technical solution adopted by the present invention is: a preparation method of a wearable visible and infrared dual-band stealth material, comprising the following steps: using a double-pass porous material as a substrate, and evaporating gold particles on the substrate material by electron beam evaporation to form a composite device of the substrate material and gold; the substrate is provided with a plurality of parallel distributed through holes, and the aperture of the through holes is 80 to 200 nm. During electron beam evaporation, the gold particles are sprayed only to the first side of the substrate material, the first side is one side connected to the through holes, and the gold particles are deposited on the first side and the inner wall of the through hole connected to the first side, so as to form a continuous gold film structure on the first side;

[0008] placing the formed composite device in a reaction solution to react, dissolving the base material in the reaction solution, leaving a gold structure, wherein the gold structure includes a gold film deposited on the first side surface and a gold column deposited on the inner wall of the through hole;

[0009] A high temperature resistant metal oxide is deposited on one side where the gold pillar is set, and the deposition thickness is in nanometer size.

[0010] As a preferred solution, the deposition rate of the gold particles during electron beam evaporation is 1-8 a / s, the thickness of the gold film deposited on the first side is 200-500 nm, and the height of the gold column deposited on the inner wall of the through hole is 250-350 nm.

[0011] The wearable visible and infrared dual-band stealth material prepared by the above scheme includes a gold film and gold pillars distributed on one side of the gold film, wherein a plurality of gold pillars are evenly distributed on the gold film in an array structure, and the gold pillars are hollow structures.

[0012] The beneficial effects produced by the present invention include: the film prepared by the present invention mainly includes two parts, one is a gold nano-columnar structure composed of gold particles, and the other is a bottom gold film. According to the characteristics of the coating process, it can be known that the gold particles constituting the gold column have a certain size distribution range (1-80nm), and due to the plasmon resonance hybridization effect of the metal nanoparticles, the material has a high absorptivity in the visible band (0.38-0.78μm). At the same time, due to the intrinsic low infrared emissivity of the gold film and the gold particles, the prepared structure also has a low emissivity in the 3-5μm and 8-14μm bands. The visible band absorptivity is as high as 91.2%, and the emissivity at 3-5μm and 8-14μm is as low as 8.7% and 3.5% respectively, showing good visible light and infrared dual-band stealth in a dark environment.

[0013] The film prepared by the present invention has a nanometer-scale thickness, is light in weight, and has good adhesion. Since the thickness of the gold film is controlled at 250nm during the preparation process, and the height of the gold column formed after etching is 300nm, the overall thickness of the material is about 0.6μm, and the weight is very light, which has a display advantage in practical application fields. In addition, the film has good adhesion and can be well attached to any complex surface.

[0014] The thin film prepared by the present invention has wearable potential. In the preparation process, since a porous material is used as a template and the gold film formed on the surface does not block the pores of the template when the deposition thickness is 250nm, the sample finally prepared has air-permeable pores, and thus has wearable potential.

[0015] The film prepared by the present invention has excellent high-temperature stealth performance. First, during the preparation process, a 10nm thick SnO 2 The protective layer is used to protect the sample, so the sample can still maintain its original structure at a high temperature of 400°C without structural collapse and failure. In addition, since the prepared sample has an extremely low emissivity, its stealth effect is still excellent at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the gold array structure in the present invention;

[0017] Figure 2 Optical photograph of the material of Example 1;

[0018] Figure 3 Infrared photo of the material of Example 1;

[0019] Figure 4 A top view of the material structure surface of Example 1;

[0020] Figure 5 A cross-sectional view of the material of Example 1;

[0021] Figure 6 Spectrum of the material of Example 1;

[0022] Fig. 7 (a) is an optical photograph of the material of Comparative Example 1;

[0023] Figure 7(b) is an infrared photograph of the material of Comparative Example 1;

[0024] FIG8 (a) is a SEM top view of the material of Comparative Example 1;

[0025] Figure 8(b) is a SEM cross-sectional view of the material of Comparative Example 1;

[0026] Fig. 9 Spectrum of the material of Comparative Example 1;

[0027] Figure 10 (a) Visible light photograph of the material of comparative example 2

[0028] Figure 10(b) is an infrared photograph of the material of Comparative Example 2;

[0029] Fig.11 SEM top view of the material of Comparative Example 2;

[0030] Fig.12 SEM cross-sectional image of the material of Comparative Example 2;

[0031] Fig.13 Spectrum of the material of Comparative Example 2;

[0032] FIG14a(i), FIG14a(ii) and FIG14a(iii) are respectively a daylight optical photograph, a dark environment optical photograph and an infrared photograph of the material of Example 1 after being attached to the edge of a cube;

[0033] FIG14b(i), FIG14b(ii) and FIG14b(iii) are respectively a daylight optical photograph, a dark environment optical photograph and an infrared photograph of the material of Example 1 after being attached to the top corner of an irregular polyhedron;

[0034] FIG14c(i), FIG14c(ii) and FIG14c(iii) are respectively a daylight optical photograph, a dark environment optical photograph and an infrared photograph of the material of Example 1 after being attached to the side of a cylinder;

[0035] FIG15( a ) is a visible light display of the film material of Example 1 after being attached to the glove;

[0036] FIG15( b ) is an infrared image of the film material of Example 1 attached to the glove;

[0037] Fig.16 Example 1: High temperature performance display diagram of thin film material;

[0038] Fig.17 Example 1 is a graph showing the change in the radiation temperature of the thin film material as a function of the actual temperature. DETAILED DESCRIPTION

[0039] The present invention is further described and explained in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific implementation methods.

[0040] The terms involved in the present invention are explained below.

[0041] Plasmon: The incident light resonates with the free electrons in the metal, and exhibits near-field field intensity enhancement at the resonant wavelength. For metal nanoparticles, the light intensity is strongly localized around the nanoparticles, and the light absorption cross section of the plasmon nanoparticles is greatly improved, so that the propagating light field can be efficiently captured and concentrated in its near-field region.

[0042] Double-pass AAO: A porous aluminum oxide film with through holes on both sides and a quasi-periodic structure.

[0043] Absorption rate: refers to the ratio of the light intensity absorbed by an object to the total incident light intensity. Generally, the absorptivity is obtained by measuring the reflectivity R and the transmittance T and calculating 1-RT.

[0044] Emissivity: A physical quantity that measures the relative strength of an object's ability to release energy in the form of thermal radiation. The emissivity of an object is equal to the ratio of the energy emitted by the object at a certain temperature to the energy radiated by a black body at the same temperature.

[0045] The present invention adopts a method of depositing gold particles on a double-pass porous material substrate, and utilizes the plasmon effect combined with the intrinsic properties of gold to form a wearable material with dual stealth in the visible and infrared, wherein the substrate has a plurality of through holes arranged in parallel, and parallel means that the central axes of the through holes are parallel to each other. The shape of the substrate is not limited, and is preferably a sheet, the sheet-shaped substrate includes a first side surface and a second side surface, the through holes penetrate the first side surface and the second side surface, and the through holes are distributed on the substrate in an array structure.

[0046] Gold particles are deposited on the substrate by electron beam evaporation, specifically, only on one side of the connecting through hole, which is referred to as the first side below. During the deposition process on the first side, gold particles will be deposited on the first side and the connected through hole. During the deposition process or after the deposition, a connected gold film is formed on the first side. The connection mentioned here means that the film is an integrated structure, not a non-porous structure on the film. At the same time, gold particles will be deposited on the inner wall of the through hole to form a gold column. The gold particle deposition method uses electron beam evaporation. During the deposition process, a focused electron beam with a certain energy bombards the gold target material. The kinetic energy of the electron beam is converted into huge heat energy to evaporate gold atoms. The evaporated gold atoms enter the surface of the substrate on the one hand, and form a connected gold film after a certain thickness is deposited. On the other hand, the evaporated gold atoms enter the pores of the substrate, collide with each other, aggregate, and finally adhere to the side wall to form gold nanoparticles. Electron beam evaporation controls the size of gold particles by controlling the deposition rate, so that the gold particle size varies within 0-100nm, so that the gold can be formed into extremely fine particles of several nanometers by controlling the rate. After gold particles are deposited on the substrate, a composite device of the substrate material and the gold material is formed. The composite device is placed in a reaction solution to etch away the substrate material. After etching, only the gold structure is retained. The gold structure includes a gold film and gold pillars. The gold pillars are distributed in an array on the gold film, preferably evenly distributed. On the one hand, the even distribution can make each part of the material have uniform optical properties, and on the other hand, it can avoid light leakage caused by the large distance between the gold pillars. During the etching process, due to the mutual adhesion between the gold particles near the hole mouth in the through hole, the gold pillars can be formed to be bonded to the gold film under the effect of self-support. The gold particles far from the hole mouth will fall into the solution after the substrate is etched away due to their fine particles and loose arrangement, thus finally forming a gold pillar array supported by the gold film.

[0047] The gold film is formed by gold particles deposited on the first side, and the gold column is formed by gold particles deposited on the inner wall of the through hole. The gold particles on the gold column generate localized plasmon resonance, which makes the material highly absorbent in the visible light band, and the interaction between the gold column and the gold film makes the material low emitting in the infrared 3-5 micron band. After obtaining the gold structure, a high-temperature resistant metal oxide is deposited on one side of the gold column of the gold structure, and the deposition thickness of the oxide is nanometer-sized. Since the size or arrangement structure of the gold structure after etching and the gold particles forming the gold column play a decisive role in the regulation of the light band, the deposition of high-temperature resistant metal oxide can improve the thermal stability of the material on the one hand, so that it will not collapse at high temperature, and on the other hand, it will not affect the optical properties of the gold structure.

[0048] The base material uses a double-pass AAO template, which is easy to etch, has a stable structure, and has a certain hardness in a small size. In the case of micron-level or even nanometer-level thickness, it can still maintain a stable structure when gold particles are deposited at high temperature. The diameter of the through hole on the double-pass AAO template is 80-200nm, and the electron beam evaporation deposition rate is 1-8a / s. The deposition is stopped when the thickness of the gold film is 200-500nm. The gold structure formed under this setting can not only make the gold film form a connected membrane structure, but also the gold particles deposited in the hole form localized plasmons, achieving visible high absorption, and under this setting, the height of the gold column formed is 250-350nm. On the one hand, the sum of the height of the gold column and the thickness of the gold film makes the material have ultra-thin and lightweight characteristics. On the other hand, the height of the gold column makes the material have low emission in the infrared band, achieving infrared stealth. Under this setting, the through holes on the substrate are not blocked, so the resulting gold film has many holes. At the same time, there are pores between the gold particles that form the gold pillars. The holes on the gold film and the pores on the gold pillars make the material have good air permeability and wearability.

[0049] When etching the substrate material, the etching solution is NaOH solution, HF solution or H 3 PO 4 The three solutions can completely etch away the double-pass AAO at this temperature without affecting the chemical and physical stability of the gold structure. 2 or Al 2 O 3 , preferably SnO 2 The deposition method is atomic layer deposition, and the deposition thickness is within 15nm, preferably 10nm. This setting can make SnO 2 A dense structural layer is formed outside the gold structure, which not only enables the gold structure to maintain high temperature stability, but also does not affect the optical properties of the gold structure. Metal oxide deposition methods are usually electron beam deposition, ion beam sputtering, magnetron sputtering and other deposition methods. Conventional deposition methods cannot form a dense protective layer on the nanoscale gold structure in the present invention, and thus cannot coordinate the high temperature tolerance and optical stability of the gold structure.

[0050] The gold structure of the present invention has an absorptivity of 91.2% in the visible band, and an emissivity of 8.7% and 3.5% at 3-5um and 8-14um, respectively. At the same time, due to its porous structure and micro-nano structure, it is widely used in wearable stealth.

[0051] The present invention is described in detail below by way of specific embodiments.

[0052] Example 1

[0053] A method for preparing a wearable visible and infrared dual-band stealth material is as follows:

[0054] S01 selects substrate: double-pass AAO template is used as substrate, the pore size d is 120nm, and the pore period is 1-1.5d;

[0055] S02 gold particle deposition: the double-pass AAO template is placed in an electron beam evaporation chamber for gold deposition, with a deposition rate of 5a / s and a deposition thickness of 250nm; during the deposition process, a focused electron beam with a certain energy bombards the gold target, and the kinetic energy of the electron beam is converted into huge heat energy to evaporate the gold atoms. On the one hand, the evaporated gold atoms enter the surface of the AAO template and form a connected gold film after deposition of a certain thickness. On the other hand, the evaporated gold atoms enter the through holes of the AAO template, collide with each other, aggregate, and finally adhere to the inner wall to form gold nanoparticles. Since gold atoms tend to gather at the orifice, the particle size formed at the orifice is larger. The overall size distribution in the hole is large at the top and small at the bottom, with the particle size close to the orifice at the top and the particle size far away from the orifice at the bottom. The particle size is 1 to 72nm;

[0056] S03 Etching substrate: Place the deposited template in a sodium hydroxide solution with a concentration of 3 mol / L, react at 60°C for 5 hours, and completely remove the AAO template. Due to the mutual adhesion between particles in the pores, especially at the pore mouth, during the etching process, these particles are retained as self-supporting nano-columnar structures, and only a small number of isolated and dispersed particles fall into the solution. The final structure formed is a gold array structure supported by a gold film, such as Figure 1 , including a gold film 1 and a gold column 2, the gold column 2 is formed by the accumulation of gold particles, and light is incident from the side where the gold column is set. In the figure, A is visible light, and there is no reflection after the visible light is incident, and B is infrared light, and the material has no infrared emission;

[0057] S04 performs atomic layer deposition (ALD) on the side with the gold pillar structure after etching, and the deposited material is 10nm SnO 2 , as a protective layer.

[0058] When the prepared stealth material is worn, the side with the gold column structure (hereinafter referred to as the structural side) faces outward, and the side with the gold film (hereinafter referred to as the non-structural side) faces inward. Figure 2 The circular black area is the material. It can be seen that the material has high absorption under visible light, achieving visible light invisibility. Infrared pictures are as follows Figure 3 , which is a photo taken when the material of this embodiment is placed on a heating platform. The heating platform is in a high temperature state. The red area in the picture is the heating platform, the middle blue area is the area where the sample material is placed, and the surrounding blue area is the environment around the heating platform. The piece where the sample material is placed is blue, which is close to the color of the surrounding environment in the infrared photo, indicating that the prepared sample has low emissivity and good infrared stealth performance.

[0059] The stealth material obtained in this embodiment was observed by scanning electron microscope. The structural surface is as follows Figure 4 It can be seen that the gold pillars are arranged evenly, there are a lot of pores on the gold pillars, and the material has good air permeability. Figure 5 The gold column is a hollow structure and is formed by the accumulation of a large number of gold particles. The geometric dimensions of the column are 120nm in diameter and 0.3μm in height.

[0060] The reflectivity R and transmittance T of the material surface were measured using the integrating sphere mode of the UV-VIS spectrophotometer, and the corresponding absorptivity of the film layer was calculated using 1-TR. The reflectivity R and transmittance T of the material surface were measured using the integrating sphere mode of the Fourier transform infrared spectrometer FTIR, and the corresponding absorptivity of the film layer was calculated using 1-TR. The spectrum of the material in this embodiment is shown in FIG. Figure 6 The absorptivity in the visible band is 91.2%, and the emissivity (absorption) in 3-5um and 8-14um is 8.7% and 3.5%.

[0061] The thickness of the gold film prepared in this embodiment is 250nm, the height of the gold column is 300nm, and the overall material is about 0.6μm. Due to its ultra-thin and porous structure, it is light in weight and exhibits good shape adhesion. It can be well attached to the surface of any complex shape. The material is attached to the edge position of the cubic module, the vertex position of the irregular polyhedron module, and the side of the cylindrical module. Figure 14a(i) , 14b(i) 14c(i) and 14c(i) are optical photographs corresponding to the above modules, respectively. It can be seen that the material and the module have good adhesion, without warping or bulging. The module is placed in a dark environment to observe the stealth effect of the material, such as Figure 14a(ii) , 14b(ii) As shown in Figure 14c(ii), the materials attached to each module all exhibit visible light stealth effect; infrared detection is performed on the above modules, as shown in Figure 14c(ii). Figure 14a(iii) , 14b(iii) As shown in Figure 14c(iii), the materials attached to each module show good infrared stealth effect.

[0062] To demonstrate its wearability, the material was attached to a glove, and visible light imaging was performed as shown in Figure 15(a) and infrared detection was performed as shown in Figure 15(b). It can be seen that the material shows good adhesion and shape adaptability on the glove, achieving dual-band stealth effects of visible light and infrared light.

[0063] The infrared stealth effect of the material was tested at 298k~723k. Fig.16 It can be seen that the material exhibits good infrared stealth effect at any temperature.

[0064] Place the material on a heating table and heat it at a temperature of 373K to 673K. Fig.17 ,It was found through monitoring that as the temperature of the ,heating platform increases, the material temperature becomes close to the ambient temperature or ,the surrounding air temperature, indicating that the material has low thermal radiation.

[0065] Comparative Example 1

[0066] A method for preparing a wearable visible and infrared dual-band stealth material is as follows:

[0067] S01 selects substrate: double-pass AAO template is used as substrate with a pore size of 50nm;

[0068] S02 Deposition of gold particles: The double-pass AAO template is placed in an electron beam evaporation chamber for gold deposition, with a deposition rate of 5a / s and a deposition thickness of 250nm. During the deposition process, only a very small amount of gold atoms enter the pores to form dispersed small particles, and the pores of the AAO template are blocked during the deposition process.

[0069] S03 etching substrate: put the deposited template into a sodium hydroxide solution with a concentration of 3 mol / L, react at 60°C for 5 hours, and completely remove the AAO template. Since the number of particles in the pores is small, the size is small and dispersed, they fall off completely during the etching process. The final structure is a gold film with an undulating structure on the surface;

[0070] S04 performs atomic layer deposition (ALD) on the side with the gold pillar structure after etching, and the deposited material is 10nm SnO 2 , as a protective layer.

[0071] The optical photograph of the stealth material of this embodiment is shown in Figure 7(a) and the infrared photograph is shown in Figure 7(b). The method of obtaining the photographs is the same as that of Example 1. It can be seen that the material exhibits a metallic intrinsic color under visible light and has no stealth effect; under infrared monitoring, the material exhibits a low emissivity. In summary, the material formed under this aperture only has infrared stealth. Through scanning electron microscopy observation, as shown in Figures 8(a) and 8(b), the final material formed is only a layer of gold film with an undulating structure on the surface, and there is no accumulation to form gold columns. Using the integrating sphere mode of the ultraviolet visible spectrophotometer UV-VIS, the surface reflectivity R and transmittance T of the material were measured, and the corresponding absorptivity of the film layer was calculated using 1-TR. Using the integrating sphere mode of the Fourier transform infrared spectrometer FTIR, the surface reflectivity R and transmittance T of the material were measured, and the corresponding absorptivity of the film layer was calculated using 1-TR. The measured spectrum of the material in this embodiment is shown in the figure below. Fig. 9 The absorptivity in the visible band is 31.6%, and the emissivity (absorption) in 3-5um and 8-14um is 2.1% and 0.4% respectively.

[0072] Comparative Example 2

[0073] A method for preparing a wearable visible and infrared dual-band stealth material is as follows:

[0074] S01 substrate selection: double-pass AAO template as substrate, pore size 390nm;

[0075] S02 gold particle deposition: The double-pass AAO template is placed in an electron beam evaporation chamber for gold deposition, with a deposition rate of 5a / s and a deposition thickness of 250nm. During the deposition process, due to the large pore size of the template, a large number of evaporated gold atoms enter the pores, collide and accumulate to form a large number of tightly packed gold particles with a wider size distribution range.

[0076] S03 etching substrate: Place the deposited template in a sodium hydroxide solution with a concentration of 3 mol / L, react at 60°C for 5 hours, and completely remove the AAO template. Since there are many particles in the pores, they are small in size and tightly bonded to each other, most of the particles are retained during the etching process. The final structure is a gold film supporting a gold array with a large diameter and a high height;

[0077] S04 performs atomic layer deposition (ALD) on the side with the gold pillar structure after etching, and the deposited material is 10nm SnO 2 , as a protective layer.

[0078] The optical photograph of the sample prepared in this embodiment is shown in Figure 10(a). The sample exhibits high absorption of visible light, achieving visible light invisibility in a dark environment. Infrared detection is performed on it, as shown in Figure 10(b). It can be seen that the material exhibits a certain degree of thermal radiation, which is quite different from the background color, and cannot achieve infrared invisibility. It is placed under an electron scanning microscope for observation. Fig.11 and Fig.12 It can be seen that the gold particles are large in size and present a dense structure near the orifice. The gold particles are large in size and sparse away from the orifice. The particles are small. The geometric dimensions of the gold column are a diameter of ~390nm and a height of ~1μm. The integrating sphere mode of the UV-VIS ultraviolet visible spectrophotometer is used to measure the surface reflectivity R and transmittance T of the material, and the 1-TR is used to calculate the corresponding absorptivity of the film layer. The integrating sphere mode of the Fourier transform infrared spectrometer FTIR is used to measure the surface reflectivity R and transmittance T of the material, and the 1-TR is used to calculate the corresponding absorptivity of the film layer. The spectrum of the material in this embodiment is measured as follows Fig.13 , the absorption rate in the visible band is 95.0%, and the emission rate (absorption rate) in 3-5um and 8-14um is 76.4% and 20.3%. In the 390nm sample structure, the diameter is ~0.39μm, and the height of the gold pillar is 0.9-1μm. It is a sub-wavelength structure relative to the wavelength of 3-5μm light beam. Therefore, due to such a characteristic size, there may be an absorption peak in the 3-5μm light band;

[0079] At the same time, there is air inside the pillars and between the pillars in this structure. From a macroscopic perspective, the medium in the overall structure is a mixture of gold and air. In the structure made with an aperture of 390nm, the proportion of air is higher overall. Therefore, based on calculations based on the effective medium theory, it can be found that the absorption in the infrared band of 8-14μm will increase.

Claims

1. A method for preparing a wearable visible and infrared dual-band stealth material, characterized in that: The following steps are included A double-pass porous material is used as a substrate, and gold particles are deposited on the substrate material by electron beam evaporation to form a composite device of the substrate material and gold; the substrate is provided with a plurality of parallel through holes, the aperture of the through holes is 80-200 nm, the through holes lead to the first side surface of the substrate material, during electron beam evaporation, the gold particles are sprayed only to the first side surface, and the gold particles are deposited on the first side surface and the inner wall of the through hole, and the deposition rate of the gold particles during electron beam evaporation is 1-8 a / s; Placing the formed composite device in a reaction solution for reaction, dissolving the base material in the reaction solution, and leaving a gold structure, wherein the gold structure comprises a gold film deposited on the first side surface and gold pillars deposited on the inner wall of the through hole, wherein the gold pillars are distributed in an array on the gold film, wherein the thickness of the gold film is 200-500 nm, and the height of the gold pillars is 250-350 nm; A high temperature resistant metal oxide is deposited on one side of the gold structure where the gold column is arranged. The high temperature resistant metal oxide is SnO2 or Al2O3, and the deposition thickness is nanometer size.

2. The method for preparing the wearable visible and infrared dual-band stealth material according to claim 1, characterized in that: The substrate is a double-pass AAO template, and the reaction solution is a NaOH solution, a HF solution or a H3PO4 solution.

3. The method for preparing the wearable visible and infrared dual-band stealth material according to claim 1, characterized in that: The high temperature resistant metal oxide is SnO2, the deposition thickness is within 15 nm, and a dense structure layer of SnO2 is formed after deposition.

4. The method for preparing the wearable visible and infrared dual-band stealth material according to claim 3 is characterized in that: The SnO2 is deposited by atomic layer deposition.

5. The method for preparing the wearable visible and infrared dual-band stealth material according to claim 1, characterized in that: The composite device is placed in a reaction solution at a reaction temperature of 60°C.

6. A wearable visible and infrared dual-band stealth material, characterized by: It comprises a gold film and a gold column disposed on one side of the gold film, wherein the gold column is distributed on one side of the gold film in an array structure, and the gold column is a hollow microcolumn formed by the accumulation of gold particles, the thickness of the gold film is 200-500nm, the diameter of the gold particles is 1-80nm, the diameter of the gold column is 80-200nm, and the height of the gold column is 250-350nm; The light is incident from the side of the gold column, and the material has high absorption in the visible light band and low emission in the mid-infrared band.

7. The wearable visible and infrared dual-band stealth material according to claim 6, characterized in that: The material is prepared by the method for preparing the wearable visible and infrared dual-band stealth material according to any one of claims 1 to 5.

8. The wearable visible and infrared dual-band stealth material according to claim 6, characterized in that: The total thickness of the gold film and the gold column is at the nanometer level. The wearable visible and infrared dual-band stealth material has an absorptivity higher than 90% in the visible band and an emissivity lower than 5% in the infrared band.

Citation Information

Patent Citations

  • Composite material device

    CN105442014A

  • Visible-near-infrared region wide-band perfect absorber and preparation method thereof

    CN108520903A